Penyuluhan Kesehatan Gigi dan Pelatihan Penanganan Bau Mulut pada Masyarakat Kelurahan Jatipulo Jakarta Barat - Soesanto, Sheila; Pratama Sarwono, Aditya; Halim, Johni; Eddy; Yuliasari, Hani (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Bad breath, or commonly known as halitosis, is a health problem that is often overlooked. It can harm a person's daily life, including social isolation, anxiety, and discomfort. Halitosis can be divided into two types: genuine halitosis (related to oral issues) and delusional halitosis (related to false perceptions). Most cases of halitosis are caused by oral hygiene problems such as reduced saliva, dry mouth, gingivitis, periodontitis, and the use of dentures. Specific bacteria in the mouth can produce foul-smelling compounds known as volatile sulfur compounds (VSCs), such as methyl mercaptan and hydrogen sulfide. Additionally, halitosis can also result from systemic issues or bad habits. It is important to provide education to the community on how to address halitosis and maintain oral hygiene. Steps like regular tooth brushing, tongue cleaning, using dental floss, and avoiding strongly aromatic foods can help reduce the risk of halitosis. In the community of RT015/RW008, Kelurahan Jatipulo, West Jakarta, this education is particularly crucial because the level of knowledge about oral health is low. Through education and training, it is hoped that the community can recognize the causes of halitosis and address the issue before seeking medical help. This will improve the quality of life for the community, boost their self-confidence, and help prevent more serious oral health.